Analisa faktor resiko mioma uteri di Rumah Sakit Umum Pusat H. Adam Malik Medan dan rumah sakit jejaring - Renny Anggraini (Fakultas Kedokteran USU, 2013)
Introduction : One of the female reproductive health problems that increase morbidity was uterine myoma. It is estimated that the incidence of uterine myoma approximately 20-30% of all women, is found in women aged 35-45 years (approximately 25%) and rarely in women 20 years and postmenopausal women. Women often give birth, less likely to progress uterine myoma compared with women who had been pregnant or just one expectant. The prevalence also increased if a family history, early menarkhe age, smoking, hypertension, and obesity.To determine the relative risk of odds ratio assessed predisposing factors uterine myoma in outpatient and inpatient care in the Adam Malik Hospital and Satelite Hospital.Methods: This study used a case-control design using secondary data analysis of a patient's medical remarks uterine myoma in the Department of Obstetrics and Gynecology Adam Malik Hospital and Satelite Hospital. The data is processed in a computerized, including descriptive statistics in this case the data is displayed in the form of frequency tables, and Confidence Interval (CI) 95%. Bivariate analyzes done using analytic comparative using chi-square test with 95% confidence level. Multivariate analysis between variables that affect using logistic regression analysis. Subjects were women diagnosed with uterine myomas based on anatomic pathology, no abdominal tumors, have complete medical records include the variables to be studied (age, menarkhe age, parity, body mass index). Samples were excluded if they do not meet the complete medical records of variables to be studied.Results: Based on the value of OR = 4.29, indicating that the risk of developing uterine myoma those aged 35-50 years 4.29 times greater than the age group < 35 years.Conclusion: With the Chi-square test statistic obtained P value < 0.05. This indicates a significant relationship between age and incidence of uterine myoma. Risk for suffering from uterine myoma those aged 35-50 years 4.29 times greater than the age group < 35 years.Keywords: uterine myoma, parity, menarche, body mass index